An Archive of Upset : the Shift from Commissioning to Curating through South Africa's Representations at the Bienal de São Paulo and the Interstitial Nexus of Leonard Tshehla Mohapi Matsoso - Dantas, Nancy Isabel (Rhodes University, Faculty of Humanities, Department of Fine Art)
This thesis explores the distinction between commissioning and curating, adopting the Bienal de São Paulo (or Bienal) as its conceptual propeller and point of departure. The thesis regards exhibitions as palimpsests, in other words, platforms built on previous conscious or sublimated models, beyond the Venetian model inaugurated in 1895. By looking at world expositions, particularly the Cape presence at the Colonial and Indian Exhibition of 1886, this project traces a lineage of commissioners, from Sir Henry Cole to Sydney Cowper through to the Director of the Pretoria Art Museum, Albert Werth. It distinguishes these men, their vision and allegiances from the curatorial model instantiated in South Africa by the late Okwui Enwezor as a consequence of the Second Johannesburg Biennale, held in 1997. The aim of this research has been to provide a partial but crucial account of this shift, and to remain attentive to the silences and deletions, to what happens in the interstice, at transitionary moments of 'betweenness.' I ask that readers consider the 1979 Bienal as an instance of an interstice where the occluded and silenced ghost of modernist artist Leonard Tshehla Mohapi Matsoso, who represented South Africa at the 1973 edition of the Bienal, garnering a substantial award for his work in drawing, resides. Matsoso was the first and only Black South African artist to receive this accolade. This thesis posits that Matsoso's absence from the exhibition in 1979, an exhibition where he would rightly have featured, constitutes a curatorial haunting, wedged in the archive of the Bienal's history, and an opportunity for revision and evaluation of commissioning vis-àvis curating. In reading the exhibition histories' archive "along the grain" (Stoler 2002), the commissioner emerges as a man of letters, a privileged social category found in the archive; a colonial authority whose status was founded as much on his display of European learning as on his studied ignorance of local knowledge; an implementer of the taxonomic state and modernist art historical canon (in the case of Werth); a cultivator of the fine arts of deference, dissemblance and persuasion. At a later stage and moment of dissonance and disruption, the independent curator emerges to reconsider, question and expand the canon, distancing him/herself from the (South African) State to serve the artist or artists and a wider community. This research aims to contribute, albeit in a small way, to a reappraisal of the position of Leonard Tshehla Mohapi Matsoso in South African modernism, and the distinction between commissioning and curating.
Keywords: Bienal Internacional de São Paulo; Curatorship; Art -- Commissioning; Art -- Political aspects; Matsoso, Leonard Tshehla Mohapi